2010
DOI: 10.1007/s11695-010-0158-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Gastric Banding in Over 60s

Abstract: Laparoscopic gastric banding can markedly improve quality of life for morbidly obese over 60s. Health gains are significant, but medication use is not substantially altered. Gastric banding is an ideal weight loss operation for this age group due to its safety and efficacy, and the primary goal should be quality-of-life improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…Clough et al [14] also concluded that medication use was not substantially altered after LAGB. In the current study, we focused on hypertension, diabetes, reflux, sleep apnea, and hypercholesterolemia and calculated the mean number of comorbidities each patient had.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clough et al [14] also concluded that medication use was not substantially altered after LAGB. In the current study, we focused on hypertension, diabetes, reflux, sleep apnea, and hypercholesterolemia and calculated the mean number of comorbidities each patient had.…”
Section: Discussionmentioning
confidence: 99%
“…With more possible years to live, more patients are turning to bariatric procedures to improve their quality of life. Contrary to the reports in the open era of bariatric procedures [5,11], many recently reported the safety of laparoscopic bariatric procedures in the elderly [12][13][14][15][16][17][18][19][20]. Most of these Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Freys et al [9] reported a significant improvement in QOL in 73 banding patients but reported a high number of complications (38%) that resulted in reoperation. A more recent study by Clough et al [10] reported marked improvement in physical, mental, emotional and social QOL in gastric banding patients over the age of 60 although they experienced less excess weight loss than their younger cohorts.…”
Section: Introductionmentioning
confidence: 97%
“…[7][8][9] For instance, a meta-analysis which was conducted by Buchwald et al 10 indicated that LAGB results in 45.5% weight excess loss and comorbidity resolution of the patients: type 2 diabetes in 80.2%, hyperlipidemia in 71%, hypertension in 71.5%, and sleep apnea in 55.6% of patients. However, safety and efficiency of LAGB in long term (R5 years) is inconsistent.…”
mentioning
confidence: 99%